Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.neurobiolaging.2007.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β impairs brain derived neurotrophic factor-induced signal transduction

Abstract: The expression of IL-1 is elevated in the CNS in diverse neurodegenerative disorders, including Alzheimer's disease. The hypothesis was tested that IL-1β renders neurons vulnerable to degeneration by interfering with BDNF-induced neuroprotection. In trophic support-deprived neurons, IL-1β compromised the PI3-K/Akt pathway-mediated protection by BDNF and suppressed Akt activation. The effect was specific as in addition to Akt, the activation of MAPK/ ERK, but not PLCγ, was decreased. Activation of CREB, a targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
142
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(157 citation statements)
references
References 83 publications
(127 reference statements)
8
142
0
2
Order By: Relevance
“…First, inflammation can influence phosphorylation of BDNF's receptor (TrkB), interfering with BDNF signaling (Cortese et al, 2011); and subsequent intracellular signal transduction can be impaired by inflammatory cytokines such as IL-1 (Tong et al, 2008). Both processes could impact depression more in those who start out with low BDNF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, inflammation can influence phosphorylation of BDNF's receptor (TrkB), interfering with BDNF signaling (Cortese et al, 2011); and subsequent intracellular signal transduction can be impaired by inflammatory cytokines such as IL-1 (Tong et al, 2008). Both processes could impact depression more in those who start out with low BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines can decrease BDNF signaling (Cortese et al, 2011;Tong et al, 2008), as can lipopolysaccharide injections (Guan and Fang, 2006). Therefore, in addition to IFN-a's effects on serotonin , dopamine (Felger et al, 2007), glutamate (Raison et al, 2010b), and the hypothalamic-pituitary-adrenal axis (Raison et al, 2010a), a decrease in BDNF may ultimately be the reason for the development of depression during IFN-a treatment.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β levels are elevated in the brain with aging and even more so in neurodegenerative disorders, such as AD. We observed that IL-1β, under conditions when it does not compromise neuronal viability, interferes with BDNF signaling by reducing activation of the docking proteins that convey the signal from the activated Trk receptors to the Ras/MAPK and PI3-K/Akt pathways, and thus elicits a type of neurotrophin resistant state (Tong et al 2007). The functional consequences were severe, as neuronal vulnerability was increased.…”
Section: Introductionmentioning
confidence: 92%
“…Recently we examined the effect of the proinflammatory cytokine IL-1β on BDNF signaling and function (Tong et al 2007). IL-1β levels are elevated in the brain with aging and even more so in neurodegenerative disorders, such as AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation